Globalisation and the New Features of International Migration - Kasnauskienė, Gindra (Ekonomika, 2002)
An economic openness in the era of globalisation is not confined to flows of trade, investment and finance, but also to flows of services, technology, information and ideas. Given this consensus, it is surprising that little attention has been given to the role of migration in the processes of globalisation. Migration is both a result of global change, and a powerful force for further change in migrant-sending and migrant-receiving societies. Its immediate impacts are fell on the economic level, but it also affects social relations, culture, national politics and international relations. Migration inevitably leads to greater ethnocultural diversity within nation-states, transforming identities and blurring traditional boundaries. The restructuring of global economic relations has resulted in new forms of migration. First, globalisation increases labour mobility by creating an environment conducive to cross-border movement of people. It demands movements of both unskilled and highly skilled labour. Second, emergence of the “knowledge-economy” of the US and Europe is altering the traditional manner of movement of labour across borders. Third, demographic changes such as falling fertility in most developed countries is leading to population decline as well as population ageing. The influx of immigrant workers would need to be very large to fully compensate for shrinking of the working-age population in many European countries. The issue of international migration in general, and particularly vulnerable migrants such as women and illegals, thus supports the call for more scholarly consideration of the global as well as local processes to adequately conceptualise the state’s capacity and willingness to deploy international law to meet social problems.